Development of Props For Monitoring Temperature, Air Pressure, and Wind Speed to Improve Science Process Skills of High School Students - Purba, Maejistresi; Hamdani, Dedy; Gunawan, Bodi (Universitas Syiah Kuala, 2025)
Finding out whether it is possible to use props to measure air temperature, humidity, pressure, and wind speed, determining how students respond to these variables, and determining whether high school students have mastered the science process skills (KPS) associated with these variables are the goals of this study. Three experts evaluated an expert validation questionnaire to determine the viability of instructional aids. 36 high school students in the X grade were given student response questionnaires to complete in order to gather their opinions on the instructional aids. Three observers evaluated an observation sheet to determine the students' level of KPS proficiency. Research and development (RD) using the ADDIE model is the methodology used in this study. Electronic parts such an LCD, BME280 sensor, anemometer sensor, and ESP32 microcontroller were used to create the props. The main focus of tool development is the microcontroller. Temperature, humidity, and air pressure are all measured by the BME280 sensor. The anemometer sensor is used to measure wind speed. An LCD displays the sensor measurement data.The findings show that: (1) the produced props' feasibility falls into the practicable category, with an average percentage value of 93.1%. (2) With an average percentage value of 87%, students' replies to the developed results fall into the very good category. (3) With an average percentage score of 93%, KPS mastery falls into the excellent category. These results lend credence to the idea that high school students can learn KPS using the air temperature, humidity, pressure, and velocity monitoring props.